2002
DOI: 10.1046/j.1365-2486.2002.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of elevated CO2 on interspecific interactions at higher trophic levels

Abstract: We report the results of a study investigating the influence of elevated CO2 on species interactions across three trophic levels: a plant (Brassica oleracea), two aphid herbivores (the generalist Myzus persicae and the specialist Brevicoryne brassicae), and two natural enemies (the coccinellid Hippodamia convergens (ladybird) and the parasitoid wasp Diaeretiella rapae). Brassica oleracea plants reared under elevated CO2 conditions (650 ppmv vs. 350 ppmv) were larger and had decreased water and nitrogen content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 37 publications
3
73
0
Order By: Relevance
“…Concerning the searching behavior of predators, Vuorinen et al (2004) showed that, unlike plants grown under ambient CO 2 , the spined soldier bug Podisus maculiventris (Say) does not discriminate herbivore-damaged plants from intact plants under elevated CO 2 , regardless of host plant cultivar. Other results tend to show similar consumption rates under both ambient and elevated CO 2 conditions for Hippodamia convergens Guérin-Méneville (Stacey and Fellowes 2002), regardless of the aphid species being predated on. Two other studies conducted in the early 2000s investigated the impact of natural enemies on the population dynamics of tree aphid species.…”
Section: Atmospheric Changes Affect Interactions With Natural Enemiesmentioning
confidence: 71%
See 3 more Smart Citations
“…Concerning the searching behavior of predators, Vuorinen et al (2004) showed that, unlike plants grown under ambient CO 2 , the spined soldier bug Podisus maculiventris (Say) does not discriminate herbivore-damaged plants from intact plants under elevated CO 2 , regardless of host plant cultivar. Other results tend to show similar consumption rates under both ambient and elevated CO 2 conditions for Hippodamia convergens Guérin-Méneville (Stacey and Fellowes 2002), regardless of the aphid species being predated on. Two other studies conducted in the early 2000s investigated the impact of natural enemies on the population dynamics of tree aphid species.…”
Section: Atmospheric Changes Affect Interactions With Natural Enemiesmentioning
confidence: 71%
“…There were several noticeable differences in the methods used by each study. For example, the difference in the CO 2 concentration between the ambient and elevated treatments was lower in the study by Stacey and Fellowes (2002) compared with Klaiber et al (2013). Also, a lower modification in CO 2 concentration could lead to a lower impact on parasitoid efficiency.…”
Section: Atmospheric Changes Affect Interactions With Natural Enemiesmentioning
confidence: 76%
See 2 more Smart Citations
“…Recent research has highlighted the key role of competition between C 3 crop and C 4 weed species under different climate and CO 2 concentrations (27). CO 2 -temperature interactions are recognized as a key factor determining plant damage from pests in future decades; CO 2 /precipitation interactions will be likewise important (58,59). Most studies continue to investigate pest damage as a separate function of either CO 2 (60-63) or climate, mostly temperature (64)(65)(66).…”
Section: Impacts On Weed and Insect Pests Diseases And Animal Produmentioning
confidence: 99%